Synthesis of eco-friendly ternary sulfide nanocrystals using a new sulfur–decene reagent in hydrocarbons - Shuklov, Ivan A.; Lim, Vladimir V.; Shalagin, Alexander Yu.; Seraja, Alexandra V.; Vershinina, Olesja V.; Zirnik, Gleb M.; Vinnik, Denis A.; Ivanov, Victor V. (Frontiers in Nanotechnology, 2026)
A new, highly reactive sulfur precursor was synthesized by dissolving elemental sulfur in 1-decene at an elevated temperature of 170 °C in a pressure tube, enabling the preparation of semiconductor sulfide nanocrystals (NCs) with diverse compositions and morphologies. By application of this new reagent, we demonstrated the preparation of eco-friendly ternary sulfide ABS2 NCs (A = Cu and Ag; B = Ga and In). The chemical composition of this sulfur reagent was analyzed by spectroscopic methods, and reactive species were revealed. The dependence of the morphology, size, and optical properties of CuInS2 NCs on the applied reagents and solvents was studied in detail. Hexadecane was identified as the solvent providing the narrowest distribution among hydrocarbons. Ag9GaS6 colloidal NCs were obtained for the first time by applying the new sulfur precursor and were fully characterized. All nanoparticles were characterized by optical spectroscopy, XRD, TEM, EDX, XPS, Raman spectroscopy, and IR. Detailed Fourier-transform infrared (FT-IR) analysis of ABS2 NCs revealed the mixed nature of the ligand shell.